Unlocking Malaysia’s Transformation to a Digital Future: The Potentials of the Economic Performance - Hui Nee AuYong; Senadjki Abdelhak; Iddrisu Mohammed Awal; Seuk Wai Phoong; Ganapathy Thavamalar, (Journal of Human Development and Communication (JoHDeC), 2025)
The purpose of this study is an analysis of digital transformation factors that shape the economic development of the digital economy. Based on interviews, the study contributes to this understanding by identifying the main paths that would shape a future scenario in which Industry 4.0 will lead. study describes the problems for the development of the digital economy. This study investigates drivers and barriers to digital economy. Based on the analysis, it is understood that the swift digitalisation undoubtedly contributes to improved economic performance as well as the environmental and societal implications. Participants elaborated the barriers to digital economy, including skills needed and availability of quality internet infrastructures. This will be a pragmatic reference in the making of government policies for economic growth through digital economy while taking into consideration the ageing society. It was concluded that a more active political and societal influencing of the digitalisation processes is necessary to make digitalisation effect for environmental sustainability. This study contributes to the digital economy development literature by providing information on both the positive and negative externalities of the digitalisation.